Theoretical reflections on Aesop’s fable in the 18th century Russia - Warda, Anna (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2010)
In the present paper describes theoretical statements of the 18th century Russian authors are described on Aesop's fable published in the introductions, forewords, dedicatory inscriptions to the collections of fairy tales. This literary genre appeared in Russia at the beginning of the 17th century. In 1607, Fyodor Gozvinsky translated Aesop's fables from Greek into Old Church Slavonic (prose). Next two also prosaic translations of works of antique fabulist were prepared in 17th century by Andrey Vinyus and Pyotr Kashinskiy. In 18th century, Sergey Volchkov translated the German translation of a French collection of fairy tales by Aesop and other antique and modern fabulists.